Prioritisation of Problems in Public Health Programme Planning Using The Difficulty Usefulness Method: Scoping Review - Binti Sukartini; Achmad Zakaria; Ade Armada Sutedja; Herin Mawarti (Poltekkes Kemenkes Tanjung Karang, 2024)
The difficulty-usefulness method is not widely known as a prioritization method. Some researchers have used this method in prioritization, but no researcher has reviewed the difficulty-usefulness method, the elements used, or the development of this method. This scoping review examines the difficulty-usefulness method in priority setting, the elements used, and the development of this method. This scoping review follows the five-stage framework of Arksey and O'Malley. A database search used keywords for literature published between January 2014 and June 2024. Data were organized, summarized, and presented in tables based on various themes. Eight studies were reviewed that utilized the difficulty-usefulness method in improving e-learning activities, preventing pesticide usage risks, selecting contraceptive methods, determining healthy family indicators, and determining community-based disaster preparedness parameters. The elements used in priority setting were aligned with the activities or issues to be improved or enhanced. These elements were determined through focus group discussions (FGD) and previous research results. The development of the difficulty-usefulness method has been carried out by several researchers, including the arrangement of elements in a pyramid structure, weighting attributes, and grouping elements into quadrants. The effectiveness of the difficulty-usefulness method has not yet been assessed, and there is still significant potential for further development.